2017
DOI: 10.5812/ircmj.13676
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Saffron Aqueous Extract and Its Main Constituent, Crocin, on Health-Related Quality of Life, Depression, and Sexual Desire in Coronary Artery Disease Patients: A Double-Blind, Placebo-Controlled, Randomized Clinical Trial

Abstract: Background: Depression and sexual problems are common in patients with coronary artery disease (CAD) and can influence their quality of life. Objectives: The aim of this study was to compare the efficacy of saffron and its main constituent, crocin, in improving mental and sexual health and ultimately quality of life in CAD patients. Methods: This double-blind, placebo-controlled, randomized clinical trial was carried out during 8 weeks in 3 groups, including 1 placebo and 2 intervention groups. The study sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…Consequently, we considered these two papers as one RCT. Therefore, a total of 11 placebocontrolled, randomized trials with 531 patients were included in the qualitative analysis [21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Consequently, we considered these two papers as one RCT. Therefore, a total of 11 placebocontrolled, randomized trials with 531 patients were included in the qualitative analysis [21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Resultsmentioning
confidence: 99%
“…Altogether, ten articles reporting on nine trials were included in our final quantitative analysis [21][22][23][24][25][26][27][29][30][31]. Akhondzadeh et al [32] provided the baseline HAM-D scores numerically, but the outcomes were shown only graphically in a figure, therefore, we could not include the results of this trial in the quantitative analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations